Ethnic minorities and immigrants therapeutic (non)adherence: What is the role of social and cultural contexts? - Mourão,Susana Sofia Monteiro (2014)
Immigrants and ethnic minorities have been identified as vulnerable groups in health, in general, and in what concerns therapeutic non-adherence (TA) in particular; i.e., (not)following health-care providers therapeutic recommendations. The general aim of this paper is presenting a literature review of immigrants/ethnic minorities TA determinants. We will start by highlighting the reasons as to why immigrants/ethnic minorities therapeutic (non)adherence should be a topic of concern. Then, we will present a review of the main determinants of immigrants/ethnic minoritiesTA, at different levels of analysis (e.g., broad structural level; social and community networks; material and social conditions) and emphasize that non-adherence among immigrants/ethnic minorities is mostly non-intentional, seeing as how it is associated with issues such as: low socio-economic conditions, language barriers and cultural mismatches. Finally, we will highlight the role of health-care providers in tackling this health-related problem and reflect about the importance of promoting development and training of health-care providers multicultural abilities.